Perlindungan hukum tenaga kerja berdasarkan peraturan perundang-undangan di Indonesia - Ngabidin Nurcahyo (Jurnal Cakrawala Hukum, 2021)
Labor protection for workers is very important because it is in accordance with the implementation of the mandate of the 1945 Constitution, particularly Article 27 Paragraph (2) concerning the rights of citizens to workers and a decent living for humanity. Given the important role of labor for state-owned and private institutions or enterprises in an effort to help workers to obtain their rights. The formulation of the problem in this writing is what is the form of legal protection for workers based on Law Number 24 of 2011 concerning the Social Security Administering Body (BPJS) and what is the responsibility of the employer if there are workers who are not registered as BPJS participants. The result of this research is that the protection for workers in the BPJS Law is that there is an obligation for employers to register their workforce into BPJS membership and the responsibility of employers if they do not register BPJS membership is that there are sanctions ranging from written warnings, fines, and cannot get certain public services.How to cite item: Nurcahyo, N. (2021). Perlindungan hukum tenaga kerja berdasarkan peraturan perundang-undangan di Indonesia. Jurnal Cakrawala Hukum, 12(1), 69-78.doi:10.26905/idjch.v12i1.5781.